Aktivitas Inhibisi Xantin Oksidase dan Antioksidan Ekstrak Etanol Daun, Batang, serta Kombinasinya dari Serai (Cymbopogon citratus) secara In Vitro - Besse Illang Sari; Siti Khairunnur; Andi Yanti Puspita Sari; Muhammad Mulyadi Nahrun (Lembaga Pengembangan Kinerja Dosen, 2025)
Lemongrass (Cymbopogon citratus) is a plant known to contain various bioactive compounds with potential antioxidant properties as well as xanthine oxidase (XO) inhibitory activity. This study aimed to evaluate the phytochemical content, antioxidant activity, and XO inhibitory potential of ethanol extracts from the leaves, stems, and their combination. Phytochemical screening revealed that all extracts contained alkaloids, flavonoids, and terpenoids, while phenolic compounds were detected only in the leaf extract and the combined leaf–stem extract. Antioxidant activity assays demonstrated that all extracts exhibited very strong antioxidant activity, with IC₅₀ values below 50 ppm, indicating a significant potential to scavenge free radicals. In the XO inhibition assay at a concentration of 200 ppm, the ethanol extract of lemongrass stems showed the highest inhibitory activity at 81.37%, followed by the leaf extract at 48.08% and the combined leaf–stem extract at 33.65%. Overall, these findings suggest that the ethanol extract of lemongrass stems is the most promising natural source of antioxidants and has the greatest ability to inhibit xanthine oxidase activity, indicating its potential development as a functional ingredient for health applications.